The law of internal armed conflict - Moir, Lindsay (Cambridge University, 2013)
Moir examines the laws designed to protect civilians in internal armed conflict. He traces the development of international law from the nineteenth century to conflicts in Rwanda and the former Yugoslavia; how human rights can protect during armed conflict; and how effectively (and by whom) the rules can be enforced.